TPS 3R DAN ECO ENZYME SOLUSI MOJOWARNO UNTUK MENGATASI MASALAH SAMPAH DAN MEWUJUDKAN LINGKUNGAN BERSIH - Nurhayati, Nurhayati; Yusron , Naufal (STIE PGRI Dewantara Jombang, 2025)
Waste management in Mojowarno District, Jombang Regency still faces various obstacles, such as lack of public awareness in sorting waste, limited processing facilities, and minimal branding and marketing of recycled products. The Community Service Team collaborated with TPS 3R Mojowarno to improve the effectiveness of waste management and introduce eco enzyme as a solution for utilizing organic waste. The steps taken include creating logo designs and product packaging, assisting in eco enzyme production, and socializing waste management with the 3R principle. In addition, the Jombang Regency Environmental Service (DLH) was also invited as a resource person in sustainable waste management education. The results of the activity showed an increase in public understanding of waste sorting and the benefits of eco enzyme. TPS 3R recycled products began to be widely known after improvements in packaging and branding. In the future, this program is expected to continue by involving more people and expanding the marketing network for recycled products